Characteristics of auroral vortices observed by multiple imagers and EISCAT radar - Tanaka, Yoshimasa; Ogawa, Yasunobu; Kadokura, Akira; Kauristie, Kirsti; Enell, Carl-fredrik; Brändström, Urban; Sergienko, Tima; Gustavsson, Björn; Whiter, Daniel; Kozlovsky, Alexander; Miyaoka, Hiroshi; Kosch, Mike (2017)
18th EISCAT symposium Session E4: Aurora and airglow May 30 (Tue), Poster Session conference object